Tensile behavior of ultra-high-performance fiber-reinforced concrete (UHPFRC) structure with cold joints. (15th December 2022) - Feng, Zheng; Li, Chuanxi; Ke, Lu; Yoo, Doo-Yeol
Highlights: Twenty-eight unreinforced UHPFRC cold-joint specimens and 16 reinforced UHPFRC cold-joint specimens are tested using a direct tension test setup. The effects of the interface roughening method, steel fiber content and length, interfacial reinforcement ratio, and embedment length on the tensile behavior of UHPFRC cold joints are evaluated. The roughening methods using high-pressure water jet and uneven plastic formwork are highly effective for obtaining good bond performance of UHPFRC cold joints. The steel fibers distributed at the cold joint interface can enhance the tensile strength and toughness of UHPFRC cold joints. Abstract: Ultra-high-performance fiber-reinforced concrete (UHPFRC) structures comprise connection joints, which are typically the weakest part. Appropriate joint construction can improve the force-transfer performance of UHPFRC structures. In this study, the effects of the interfacial roughening method, steel fiber content and length, interfacial reinforcement ratio, and embedment length on the tensile behavior of UHPFRC cold joints are investigated via direct tension tests. The test results indicate that the roughening methods using high-pressure water jet and uneven plastic formwork significantly improve the bond performance of UHPFRC cold joints. Moreover, the steel fibers in the cold-joint interface enhance the tensile strength and toughness of these joints. The typical failure mode of the unreinforced UHPFRC cold joint is found to be brittle failure. By contrast, the cracking and failure surfaces shift from the cold joints to the UHPFRC matrix when the UHPFRC cold joint is well-reinforced. Furthermore, an increase in the interfacial reinforcement ratio and embedment length improves the ultimate tensile strength of the reinforced UHPFRC cold-joint specimens, whereas the minimum embedment length decreases with the interfacial reinforcement ratio (should be at least 40 mm). In addition, an equation for the minimum embedment length of reinforcing steel rebars is proposed. The proposed method can be applied to determine the effects of the parameters, tensile strengths of the UHPFRC matrix and cold joint interface, reinforcement ratio, and rebar diameter on the tensile behavior of UHPFRC cold joints.